2010
DOI: 10.1021/jf103577j
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Persistence of Atrazine in Several Field Soils with Different Atrazine Application Histories

Abstract: To assess the potential occurrence of accelerated herbicide degradation in soils, the mineralization and persistence of 14 C-labeled and non-labeled atrazine was evaluated over three months in two soils from Belgium (BS: atrazine treated 1973 BC: non-treated) and two soils from Germany (CK: atrazine treated 1986-1989; CM: non-treated). Prior to the experiment, accelerated solvent extraction of bulk field soils revealed atrazine (8.3 and 15.2 µg kg −1 in BS and CK soil), and a number of metabolites directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…Atrazine and its metabolites can persist in water and soil for decades. Jablonowski et al have demonstrated the high persistence of atrazine and its metabolites in soil [40, 41]. The accumulation of the parent compound in the soil may result in a long-term source of atrazine and its metabolites to ground water or surface waters [42].…”
Section: Resultsmentioning
confidence: 99%
“…Atrazine and its metabolites can persist in water and soil for decades. Jablonowski et al have demonstrated the high persistence of atrazine and its metabolites in soil [40, 41]. The accumulation of the parent compound in the soil may result in a long-term source of atrazine and its metabolites to ground water or surface waters [42].…”
Section: Resultsmentioning
confidence: 99%
“…Th e rationale behind this hypothesis was that recalcitrant amendments may require a specialized microbial community, a phenomenon already observed in organic xenobiotics ( Jablonowski et al, 2010), whereas easily decomposable amendments do not. In an incubation experiment, the C and N mineralization of three types of organic amendments, diff ering greatly in their chemical characteristics, were compared aft er their application to soils taken from a long-term fi eld experiment that had received one of the corresponding amendments or no amendment for 35 yr before the current experiment.…”
mentioning
confidence: 99%
“…It is important to inform, that HA was not studied in the present work, owing to its intense interaction with the soil particles, providing lower mobility in soils in comparison with AT, DEA and DIA, and as a result, HA presents low likelihood to contaminate groundwaters and surface waters. The more effective extraction methods were not investigated in this work, for instance PLE, 1,22 that could provide the quantification of the bound fraction. Notwithstanding, the results here presented suggest that the method is suitable for the extraction of the more mobile fraction of AT, DIA and DEA, and possibly for other triazines, which is the most relevant fraction for environmental evaluations.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…A traditional and low cost method that can be used for triazine extraction from soils is soxhlet, that yields efficient extraction, but it is a time and solvent consuming method. 12,19 Because of this, green extraction methods have been proposed, including ultrasonic solvent extraction (USE), 14,19 microwave assisted extraction (MAE), 15,16 supercritical fluid extraction (SFE), 20 extraction of the analytes after the shaking of the sample in the presence of an appropriate solvent, followed by solid phase extraction (SPE), 17 headspace solid-phase microextraction (HS-SPME), 21 pressurized liquid extraction (PLE), 1,12,13,22 besides the development of other miniaturized methods as reported in the literature. 14 These methods usually present appropriate results, however some authors have used a less expensive extraction method, based on a simple shaking with solvents of adequate polarity like acetonitrile or methanol and water, providing acceptable recovery values for the extraction of triazine herbicides from soils; 5,8,19 nevertheless, the extraction time is often a drawback, for instance, Mahía et al, 5 and Delgado-Moreno et al, 19 employed 24 h as extraction time.…”
Section: Introductionmentioning
confidence: 99%